Una carta inédita del Jesuita José García desde las misiones en Chiloé (1766) - Ortiz Canseco, Marta (Anales de Literatura Chilena, 2017)
Este artículo presenta una carta inédita del jesuita José García, famoso autor del Diario del viaje i navegación hechos por el Padre José García…, realizado entre 1766 y 1767. La carta, desconocida hasta hoy y hallada en la Biblioteca Nacional de España, está dirigida al jesuita José Rojo, boticario del Colegio Máximo de Lima. El tono amable del documento descubre la faceta más humana del autor, que realiza un breve recorrido sobre el estado de las misiones circulares de Cailín, narrando Jesús durante los períodos de evangelización al sur del archipiélago de Chiloé. Rescatando los puntos más importantes de la carta, la
An unpublished letter of Jesuit José García from Chiloe's missions (1766)
This article presents an unpublished letter by Jesuit Jose Garcia, author of the famous Diario del viaje i navegacion hechos por el Padre Jose Garcia..., written between 1766 and 1767. The letter, previously unknown, was found in the National Library of Spain, and it is addressed to the Jesuit Jose Rojo, pharmacist at the Colegio Maximo in Lima. The friendly tone of the document allows us to discover the most human side of the author, who writes a brief narrative about the conditions of the circular missions in Chiloe and the great hardship the priests underwent during the evangelization periods there. In the following pages I present information about the context to which the letter refers, with the aim of underlining the particularities and importance of the Jesuit missionary endeavour in Chiloe.
Keywords: Jesuitas; documentos inéditos; misiones circulares; archipiélago de Chiloé; Jesuits; unpublished documents; circular missions; Chiloe archipelago; WOS; Scopus